Regulating signal enhancement with coordination-coupled deprotonation of a hydrazone switch - Foy, Justin T. (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
Proton relay plays an important role in many biocatalytic pathways. In order to mimic such processes in the context of molecular switches, we developed coordination-coupled deprotonation (CCD) driven signaling and signal enhancement sequences. This was accomplished by using the zinc(ii)-initiated CCD of a hydrazone switch to instigate an acid catalyzed imine bond hydrolysis that separates a quencher from a fluorophore thus leading to emission amplification. Because CCD is a reversible process, we were able to show that the catalysis can be regulated and turned “on” and “off” using a metalation/demetalation cycle.